2014
DOI: 10.1007/s40436-014-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

SCADA data based condition monitoring of wind turbines

Abstract: Wind turbines (WTs) are quite expensive pieces of equipment in power industry. Maintenance and repair is a critical activity which also consumes lots of time and effort, hence making it a costly affair. Carefully planning the maintenance based upon condition of the equipment would make the process reasonable. Mostly the WTs are equipped with some kind of condition monitoring device/system, which provides the information about the device to the central data base i.e., supervisory control and data acquisition (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 29 publications
(29 reference statements)
0
30
0
Order By: Relevance
“…Models and methods of failure diagnostics in automated systems are considered in the works of the authors [4][5][6][7][8][9][10].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Models and methods of failure diagnostics in automated systems are considered in the works of the authors [4][5][6][7][8][9][10].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Methods of fault diagnostics for wind turbines controlled by SCADA are examined in work [8]. The authors provide a review of a number of diagnostic methods, including methods based on artificial neural networks, fuzzy-logic methods, and combined methods such as adaptive neuro-fuzzy inference.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In many papers of the state of the art research we can see that the selection of the variables is done manually by an expert, or based on the perception of the author according to the subsystem to analyze. Some authors, such as [29,33,42,43], include some type of reduction stage by correlations or PCA, but do not make a comparison of selection methods, or this comparison does not contain methods that include the interaction of more than two variables such as those presented in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The conditionmonitoring approach based on SCADA datasets is cost-efficient and readily available. [26][27][28] The research and application of other important parameters, based on WT condition monitoring, for example, temperature-related parameters, are mainly dependent on SCADA data. Feng et al 29 showed that the gearbox temperature rises when the gearbox efficiency decreases.…”
Section: Introductionmentioning
confidence: 99%